Relative humidity sensing using a PMMA doped Agarose gel microfiber - Irawati, Ninik; A. Rahman, Husna; Yasin, Moh; Askari, Shadi; Hamida, Belal Ahmed; Ahmad, Harith; W. Harun, Sulaiman (The Optical Society, 2017)
Humidity sensors rely on humidity-induced refractive index change in the sensing material despite the sensor configuration. Polymer-based microwires can absorb water vapor molecules and detect humidity changes without the need of further coating. However, the sensitivity-simplicity trade-off is still a challenge. Sophisticated coating methods, complex resonating structures and nano-structured films are reported as methods to enhance the device sensitivity. A simple technique, to build a high sensitivity RH sensor based on an agarose-doped Poly Methyl Methacrylate (PMMA) sensor head, is demonstrated. The waist diameter and uniform length of the PMMA doped agarose gel microfiber were measured to be 6 μm and 10 mm, respectively. The sensor can achieve power variation of up to 2.9μW in a wide relative humidity range (50-80%), and display linear response with a correlation coefficient of 98.29 %, sensitivity of 0.421 dB/%RH and resolution of 0.431%RH. This agarose-based optical sensor provides a beneficial complement to the existing electrical ones, and will promote the employment of agarose in chemical sensing techniques.